2006
DOI: 10.1038/sj.jid.5700317
|View full text |Cite
|
Sign up to set email alerts
|

[Nle4-D-Phe7]-α-Melanocyte-Stimulating Hormone Significantly Increased Pigmentation and Decreased UV Damage in Fair-Skinned Caucasian Volunteers

Abstract: Epidermal melanin reduces some effects of UV radiation, the major cause of skin cancer. To examine whether induced melanin can provide protection from sunburn injury, 65 subjects completed a trial with the potent synthetic melanotropin, [Nle4-D-Phe7]-alpha-melanocyte-stimulating hormone ([Nle4-D-Phe7]-alpha-MSH) delivered by subcutaneous injection into the abdomen at 0.16 mg/kg for three 10-day cycles over 3 months. Melanin density, measured by reflectance spectroscopy, increased significantly in all [Nle4-D-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
87
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(91 citation statements)
references
References 44 publications
2
87
0
2
Order By: Relevance
“…More recently, several studies examined the effects of [Nle 4 -D-Phe 7 ]-αMSH, a synthetic superpotent analogue of αMSH, on human skin in situ and reported increased pigmentation after a series of 10 injections [78][79][80][81]. In a larger study, injections of 65 subjects with a slow-release formulation of the same αMSH analogue over 3 months lead to an average 41% increase of melanin in subjects with high sun-sensitivity compared to a 12% increase in subjects with low sun-sensitivity, and there was no significant difference in pigmentation between sun-exposed and non-sun-exposed areas [82]. As the necessity to inject the drug on a regular basis to maintain a tan is a major drawback, there are currently attempts to develop αMSH analogs that are small enough to reach their target when administered topically.…”
Section: Stimulation Of Melanogenesismentioning
confidence: 95%
“…More recently, several studies examined the effects of [Nle 4 -D-Phe 7 ]-αMSH, a synthetic superpotent analogue of αMSH, on human skin in situ and reported increased pigmentation after a series of 10 injections [78][79][80][81]. In a larger study, injections of 65 subjects with a slow-release formulation of the same αMSH analogue over 3 months lead to an average 41% increase of melanin in subjects with high sun-sensitivity compared to a 12% increase in subjects with low sun-sensitivity, and there was no significant difference in pigmentation between sun-exposed and non-sun-exposed areas [82]. As the necessity to inject the drug on a regular basis to maintain a tan is a major drawback, there are currently attempts to develop αMSH analogs that are small enough to reach their target when administered topically.…”
Section: Stimulation Of Melanogenesismentioning
confidence: 95%
“…In a more recent clinical trial, systemic administration of NDP-MSH, which led to increased pigmentation, was found to prevent sunburn and reduce UV-induced DNA damage, particularly in individuals with low minimal erythemal dose (i.e. with light skin color who burn readily) [8]. These results provide proof of principle for the efficacy of a-MSH analogs in photoprotection, and demonstrate that despite melanocortin synthesis in the skin and its increase upon UV exposure, administration of a-MSH analogs potentiates the paracrine effects of endogenous melanocortins.…”
Section: Melanocortin Analogsmentioning
confidence: 99%
“…20 The increase in pigmentation in response to NDP-MSH was due to stimulation of eumelanin synthesis without any effect on pheomelanin synthesis. This and the early study by Levine et al 19 relied on multiple injections of volunteers with NDP-MSH, which is not a practical method of delivery.…”
Section: _-melanocortin Analogs As Tanning Agentsmentioning
confidence: 98%
“…21 The most recent human study with NDP-MSH showed that it reduced the extent of DNA photoproducts, as well as sunburn cells (i.e., apoptotic keratinocytes), that are induced by UV irradiation, indicating reduction of UV-induced DNA damage. 20 Toxicological studies carried out with NDP-MSH demonstrated that it was not toxic or teratogenic to mice, rats or Yucatan miniature pigs (reviewed by Hadley and Dorr). 21 It did not increase the growth or metastasis of melanoma cells injected in mice, nor did it increase the growth of human melanoma tumors in SCID mice.…”
Section: _-melanocortin Analogs As Tanning Agentsmentioning
confidence: 99%